Increasing Prevalence of Nontuberculous Mycobacteria in Respiratory Specimens from US-Affiliated Pacific Island Jurisdictions - Chunrong Lin; Chad Russell; Bruce Soll; Dominic Chow; Sapna Bamrah; Richard Brostrom; Wesley Kim; Jerry Scott; Matthew J. Bankowski (Emerging Infectious Diseases, 2018)
Nontuberculous mycobacteria (NTM) respiratory infections represent a growing public health problem in many countries. However, there are limited published epidemiologic studies for the Western Pacific region. We reviewed respiratory specimens submitted to Diagnostic Laboratory Services in Hawaii, USA, for culture of Mycobacterium tuberculosis during August 2007–December 2011 to determine the NTM isolation rate. We observed a statistically significant increase in the rate of specimens with NTM isolated in respiratory culture (adjusted rate ratio per year 1.65, 95% CI 1.54–1.77; p<0.01). In contrast, the number of patients with respiratory cultures positive for M. tuberculosis showed no increase (adjusted rate ratio per year 0.98, 95% CI 0.94–1.01; p = 0.19). A 6-month subset of NTM isolates was identified by using a nucleic acid probe or 16S rRNA sequencing. M. avium complex and M. fortuitum were the most common NTM identified.